Kinship terminology of the Bau-Jagoi Bidayuh in Sarawak, Malaysia - Yvonne Michelle Campbell (Universitas Syiah Kuala, 2021)
This paper explores the kinship terms of the Bidayuh of Sarawak, focusing on the Bau-Jagoi subgroup variation as well as their cultural concept of kinship. The data for this paper was obtained through participant observation and interviews with four informants from two villages in Bau District, Sarawak, Malaysia, which are Kupuo Sarasot, located in the Jagoi area and Kupuo Barieng in the Singai area. The data analysis showed that the Bidayuh held on firmly to the Madih concept¸ in which all members of the village are considered 'one family'.  The Bidayuh kinship terms do refer to birth order but with emphasis on the older generations. Gender is not emphasized in the Bidayuh kinship terms but refers to a specific gender. Two main adjectives are added after the kinship terms, which are dari' (male) and dayung (female). The address terms also focus on the older generations while most of the younger generations are addressed by their names. These two areas, even though considered under one subgroup, have their unique practices when it comes to kinship terms.  However, due to modernization and urbanisation, the influence of the Malay and English language could be clearly seen in the Bidayuh address terms, replacing the Bidayuh equivalent.